The problem with confidence: too much and too little results in poorer achievement, inner conflict, and social inhibition - Douglas, Heather E.; Cunningham, Mitchell L.; Tisdell, Jessika; Arneson, Justin (Frontiers in Psychology, 2023)
Confidence is defined as the feelings and thoughts people have during a task that result in judgements about their performance. Evidence suggests that confidence is trait-like, but thus far research on the relative match between confidence and accuracy has been primarily restricted to over-confidence effects, and subject to the methodological flaws involved with using difference scores. We sought to answer an exploratory question in this research, whether discrepancies in ability and confidence in either direction reliably predicted individual differences on a broad-spectrum and commercially available personality test, the California Psychological Inventory (CPI260). Participants were 225 employed adults who had previously taken the CPI260 for career development purposes. They were invited to complete a measure of cognitive ability and confidence in return for feedback on the same. Data were modelled using polynomial regression and response surface analysis, to determine whether and how CPI260 personality traits were associated with matches or mismatches between accuracy and confidence in the same test. Individuals who were under-confident and those who were over-confident had lower achievement potential, less social confidence, and more inner conflict than other individuals in this sample, suggesting that both too much and too little confidence can be detrimental for human functioning.